2017
DOI: 10.1038/srep40697
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and regional presence of hymenopteran parasitoids of Drosophila in Switzerland and their ability to parasitize the invasive Drosophila suzukii

Abstract: Since its introduction into Europe the invasive Drosophila suzukii has established and spread widely, thereby entering habitats populated by native Drosophila species and their natural enemies. The highly prolific D. suzukii will likely interact with these species as a competitor, host or prey. To investigate potential interactions of D. suzukii with parasitoids, a field survey was conducted across several fruit-growing regions in Switzerland in two consecutive years. Eight species of hymenopteran parasitoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 52 publications
6
51
0
1
Order By: Relevance
“…These results suggest that L. heterotoma's virulence is not strong enough to resist the immune reaction of D. suzukii. This was also observed in other studies (Chabert et al, 2012;Kacsoh & Schlenke, 2012;Knoll et al, 2017;Poyet et al, 2013;Rossi Stacconi et al, 2017).…”
Section: F I G U R Esupporting
confidence: 78%
See 3 more Smart Citations
“…These results suggest that L. heterotoma's virulence is not strong enough to resist the immune reaction of D. suzukii. This was also observed in other studies (Chabert et al, 2012;Kacsoh & Schlenke, 2012;Knoll et al, 2017;Poyet et al, 2013;Rossi Stacconi et al, 2017).…”
Section: F I G U R Esupporting
confidence: 78%
“…These results suggest that L. heterotoma's virulence is not strong enough to resist the immune reaction of D. suzukii. This was also observed in other studies (Chabert et al, 2012;Kacsoh & Schlenke, 2012;Knoll et al, 2017;Poyet et al, 2013;Rossi Stacconi et al, 2017).However, a single female succeeded to complete its development in this study, and higher rates of successful development were observed when testing various geographic strains of the parasitoid (P. Girod A. japonica and L. japonica that attacked and developed in larvae in both substrates, Ganaspis sp. parasitized many more larvae in blueberries compared to artificial diet.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…oak galls being more suitable hosts. Some parasitoid species could have indeed avoided ACGW galls and concentrated on native hosts as infecting a new introduced host may incur a fitness cost for native parasitoids (Jones et al 2015;Knoll et al 2017). …”
Section: Acgw Infestation Rates Depend On Tree Neighbour Identitymentioning
confidence: 99%